The Success of computer crime act implementation (UU ITE No.11 year 2008) in the higher education Institution in Indonesia - Dewantara, Rizki Yudhi (Prince of Songkla University, 2014)
Thesis (M.B.A., (Public Administration))--Prince of Songkla University, 2013